Quantitative Analysis of the Cardiac Phosphoproteome in Response to Acute β-Adrenergic Receptor Stimulation In Vivo - Alican Güran (MDPI AG, 2021)
β-adrenergic receptor (β-AR) stimulation represents a major mechanism of modulating cardiac output. In spite of its fundamental importance, its molecular basis on the level of cell signalling has not been characterised in detail yet. We employed mass spectrometry-based proteome and phosphoproteome analysis using SuperSILAC (spike-in stable isotope labelling by amino acids in cell culture) standardization to generate a comprehensive map of acute phosphoproteome changes in mice upon administration of isoprenaline (ISO), a synthetic β-AR agonist that targets both β1-AR and β2-AR subtypes. Our data describe 8597 quantitated phosphopeptides corresponding to 10,164 known and novel phospho-events from 2975 proteins. In total, 197 of these phospho-events showed significantly altered phosphorylation, indicating an intricate signalling network activated in response to β-AR stimulation. In addition, we unexpectedly detected significant cardiac expression and ISO-induced fragmentation of junctophilin-1, a junctophilin isoform hitherto only thought to be expressed in skeletal muscle. Data are available via ProteomeXchange with identifier PXD025569.